(untitled) (Al-Mansour Journal, 2022)
In this paper two design of fractal geometry for microstrip antennas is presented for ultra-wideband applications. The first structure is implemented on four upright triangular patches and several iterations are applied on its initial shape. While, the second design based on the same fractal geometry with four direct coupled and other electromagnetic coupled (EMC) parasitic patches. The idea of inserted parasitic patches will make the current path became longer than the topological length, then UWB characteristic is achieved her. The computed bandwidth is 1.69 GHz for the first geometry, and it is 10.5 GHz for the second. A comparison is made up between the computed bandwidths for the two designs and the advantage of inserting the parasitic patches became clear. The comparison shows the enhancement in bandwidth for the second design. Furthermore, these structures have low profile, lightweight and are easy to be fabricated and have successfully demonstrated UWB characteristics. The simulated results show that, the proposed antenna has very good performance in impedance bandwidth with accepted radiation pattern.